Figure 9 in Recent evolution of ancient Arctic leech relatives: systematics of Acanthobdellida ... - Carle, Danielle Božena De; Gajda, Łukasz; Bielecki, Aleksander; Cios, Stanisław; Cichocka, Joanna M.; Golden, Heidi E.; Gryska, Andrew D.; Sokolov, Sergey; Shedko, Marina Borisowna; Knudsen, Rune; Utevsky, Serge; Świątek, Piotr; et al. (Zenodo, 2022)
Figure 9. Scanning electron micrographs of gonopores and posterior body regions. A, B, gonopores in a small Acanthobdella peledina (4 mm; Alaska; A) and a large Paracanthobella livanowi (11 mm; Kamchatka; B). C, D, the posterior body region for a medium-sized A. peledina (7 mm; Sweden; C) and a medium-sized P. livanowi (6 mm; Kamchatka; D). Double arrows indicate the posterior sucker; f, female gonopore; m, male gonopore; s, opening of the spermatheca. Dotted lines and Roman numerals denote segments. ... : Published as part of Carle, Danielle Božena De, Gajda, Łukasz, Bielecki, Aleksander, Cios, Stanisław, Cichocka, Joanna M., Golden, Heidi E., Gryska, Andrew D., Sokolov, Sergey, Shedko, Marina Borisowna, Knudsen, Rune, Utevsky, Serge, Świątek, Piotr & Tessler, Michael, 2022, Recent evolution of ancient Arctic leech relatives: systematics of Acanthobdellida, pp. 149-168 in Zoological Journal of the Linnean Society 196 on page 164, DOI: 10.1093/zoolinnean/zlac006, http://zenodo.org/record/7037718 ...